Kajian Hermeneutika Maqashid Al-Syari’ah sebagai Hikmah Al-Tasyri’ Hukum Wali Pernikahan dalam Kitab Al-Umm - Siti Aisyah (Fakultas Syariah Institut Ilmu Keislaman Zainul Hasan, 2016)
In Islam, every law prescribed by God has its own purpose and reason. Maqashid al-Syari’ah is the purpose of law. Therefore, the mujtahid keep trying to study and comprehend sharia texts to understand Maqashid al-Syari’ah, including the law of marriage representative. The problems of the study consist of Shafi’s’s perspectives on the law of marriage representative on book Al-umm. The study employs the review of Maqashid al-Syari’ah using hermeneutic approach. It is a normative research which involves literary study. It employs secondary data written in fiqh kitab use the comparative analysis. include the illegitimate status of marriage done by immature woman without the presence of her representative. In the maqashid al sharia analysis of hermeneutics, it is concluded that in the methodology of Fazlur Rahman, to get sense of maqashid al-syari’ah on marriage representative , is a solution for the problem solving about gender. Ijbar right, not to be a necessity reason, but used fro to pretect women whom adult yet, and for the communication media by the adult women.